Factors influencing saving behaviour: A study on Petronas Chemicals Marketing (Labuan) LTD employees / Muhammad Abdullah - Abdullah, Muhammad (UITM Sarawak,Kampus Samarahan, 2016)
Awareness in retirement is still an indistinct matter among people in Malaysia and many retirement products being introduced by financial institutions and yet the initiatives to put aside for retirement are step sided by many. Since the majority think that companies and government retirement plan should be sufficient to cover for golden years costs. Yet, many studies have revealed that money saved in companies and government pension plan may not be enough for future expenditure. In the prior study, several researchers studied saving behaviour among the young adults such as university students rather than workforce. Even though there is not many studies focus on the financial behaviour of workforce, most of the studies were just focused on particular factors. For that reason, this study is aims to look into whether peer influence (PI),financial literacy (FL) and self-control (SC) have major influence on the saving behaviour (SB) of employees in private sector. Primary data are collected using self-administered questionnaire. The samples comprised 100 private sector employees in Petronas Chemicals Marketing (Labuan)Ltd. Meanwhile, Squared Multiple Correlations and Multiple Regression Analysis are employed to identify whether the three factors have relationship with the saving behaviour of private sector employees. The findings illustrate that all the peer influence,financial literacy and self-control have positive relationship with saving behaviour despite the fact that financial literacy has the utmost impact on saving behaviour among the three independent variables. This signifies that financial understanding is playing essential roles in ensuring private sector employees to begin saving behaviour.